PENYULUHAN SUMUR RESAPAN DAN SANITASIUNTUK EDUKASILINGKUNGAN SEHAT SESUAI STANDAR KESEHATAN PADA MASYARAKAT - Arif Wibowo (Asian Journal of Innovation and Entrepreneurship, 2013)
Environmental hygiene became one of the fundamental factor for the ongoinglive a clean, healthy, and convenient. Protected from various kinds of diseases so desiredby everyone. In maintaining the cleanliness of the environment not only ourselves, butalso the community, and also the government. The lack of public attention to theenvironment is very familiar to today. Most of them think partially and only want tobenefit themselves, such asthe problem of garbage disposal is not in place, the disposalof industrial waste, air pollution, water pollution, and others. Cases concerningenvironmental hygiene problems in the always affect public health each year is alwaysincreasing. Communities also need to improve the environment and to theimplementation of development activities that can help power the harmonious andsustainable land. For that the extension services related to environmental sanitation andmanufacture of absorption wells is expected to be efforts to make people aware of theimportance of environmental health as well as providing knowledge of how to make ithappen.